Práticas educativas no ensino do Proeja: um estudo de caso no Instituto Federal de Educação, Ciência e Tecnologia do Amapá – IFAP campus Agrícola Porto Grande - (:unkn) unknown (Brasil, 2024)
National Program for the Integration of Professional Education with Basic Education in the Modality for Youth and Adult Education – PROEJA is aimed at young people and adults who were unable to complete basic training at a regular age and are seeking secondary education certification linked to professional training, as well as the continued training of teachers who work in this modality. Thus, the investigation had the general objective of understanding the educational practices developed at PROEJA within the scope of the Postgraduate Program in Professional and Technological Education – ProfEPT and Federal Institute of Education, Science and Technology of Amapa – IFAP / Porto Grande Agricultural Campus. The research is predominantly qualitative in nature and is configured as a case study, and the locus of study was IFAP/ Porto Grande Agricultural Campus. The subjects of the research were teachers of the curricular components of both the common core and the technical area who taught classes in PROEJA groups of technical courses in Agribusiness, Administration and Agriculture in the year 2023, as well as the Campus pedagogues. Bibliographic analysis and questionnaire application were used as data collection instruments/techniques. Thus, the research presents the national scenario regarding educational practices in the teaching of PROEJA, within the scope of ProfEPT, based on the survey of dissertations analyzed on the Program Observatory website, which revealed the existence of few publications regarding of the PROEJA theme, as well as the results of the research carried out at IFAP / Porto Grande Agricultural Campus. As an Educational Product, we developed, applied and validated the promotion of a Round Table with the theme, “Educational Practices in teaching PROEJA”.
Keywords: educação de jovens e adultos; práticas educativas; produto educacional; mesa redonda; CNPQ::CIENCIAS HUMANAS::EDUCACAO